2021
DOI: 10.34007/jdm.v2i1.598
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan abstraksi reflektif matematis siswa pada materi bangun ruang

Abstract: This study aims to determine the ability of reflective mathematical abstraction which consists of the ability to apply concepts, the ability to make relationships between concepts to form new meanings, and the ability to manipulate abstract mathematical objects. This research is a qualitative research with type of case study. The sample used in this study was one senior high school student of class X. The method of collecting data to find the results of the study was to use a test instrument for building quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous research on reflective abstraction using the APOS mental structure indicated that females perform better than male students with a fair category, recommending further research to improve these results (Rahmawati et al, 2018). Many studies have analyzed reflective abstraction levels from secondary school to higher education levels (Sutrisna et al, 2021(Sutrisna et al, , 2022Widiyasari et al, 2020;Yusepa, 2017). Previous research focused solely on identifying and characterizing reflective abstraction skills rather than on teaching efforts using instructional materials to train reflective abstraction skills.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on reflective abstraction using the APOS mental structure indicated that females perform better than male students with a fair category, recommending further research to improve these results (Rahmawati et al, 2018). Many studies have analyzed reflective abstraction levels from secondary school to higher education levels (Sutrisna et al, 2021(Sutrisna et al, , 2022Widiyasari et al, 2020;Yusepa, 2017). Previous research focused solely on identifying and characterizing reflective abstraction skills rather than on teaching efforts using instructional materials to train reflective abstraction skills.…”
Section: Introductionmentioning
confidence: 99%
“…In research that has been carried out (Afdila et al, 2018;Cesaria et al, 2021;Damayanti & Rufiana, 2021;T. Hidayat, 2019;Maharani & Prihatnani, 2019;Ningrum & Budiarto, 2016;Nurfajriyanti & Pradipta, 2021;Nurlaila et al, 2018;Putra et al, 2022;Rumasoreng & Sugiman, 2014;Safitri et al, 2019;Sutrisna et al, 2021). The elements, most students are wrong in determining the volume and surface area and almost all students are wrong in working on questions with the theme of flat-sided space shapes.…”
Section: Introductionmentioning
confidence: 99%